The level of blood plasma mitochondrial DNA upon acute myocardium damage in experiment - Sudakov, N.P.; Popkova, T.P.; Novikova, M.A.; Katyshev, A.I.; Nikiforov, S.B.; Pushkarev, B.G.; Goldberg, O.A.; Klimenkov, I.B.; Lepekhova, S.A.; Ezhikeeva, S.D.; Ten, M.N.; Osipov, V.G.; et al. (Вiopolymers and Cell, 2012)
The aim of the present investigation is to study the level of plasma mtDNA as a potential marker of cardiomyocyte damage in 2 and 4 h after subcutaneous injection of adrenaline and during the formed morphological alterations of the myocardium (3 days). Methods. Real time PCR. Male Wistar rats were used as the experimental animals. Results. It was shown that during the increase in the activity of cytolysis biomarkers, at the first hours after adrenaline injection, no reliable increase is observed in the level of free circulating blood mtDNA. A tendency of 2.5-fold increase in this parameter was established at the third day after adrenaline injection during the development of acute inflammatory process in the myocardium. On the whole, further researches are needed on the dynamics of mtDNA level upon acute damage of the myocardium in experimental and clinical investigations for unbiased estimation of the prospects of using the parameter in laboratory diagnostics. Keywords: mitochondrial DNA, cardiovascular diseases, adrenaline myocarditis, cytolysis biomarkers.